La movilidad humana en la red de las palabras de Estado - Avallone, Gennaro (REMHU, Revista Interdisciplinar da Mobilidade Humana, 2019)
This article aims to study contents and reasons that sustain an ethno-centric-State view about migration, based on the combination between State thought and a colonial cultural and political attitude, that reproduces the hierarchization of global population. The article proposes an epistemological and methodological critics, widely based on Abdelmalek Sayad’s writings, that questions the hegemonic way to observe and know migration. At the same time, these critics, normatively, allows to highlight the need to free migration from State words, which are dominant in the understanding oh human mobility, beginning by the recognition of migration’s historicity, power relations in which migration are made and relative autonomy of migration.